Research on Green Building Engineering Management Based on Sustainable Development - Zhu, Jiarui (Transactions on Engineering and Technology Research, 2024)
With the development of green building and sustainable building, the emergence of innovative project management is an inevitable trend of the times. This paper mainly studies the green building project management based on sustainable development. First, the relationship between green building and sustainable building is analyzed under the concept of green building, which leads to a series of reforms and upgrades that construction management needs to face. Then, by comparing the differences between old and new project management models, the methods of applying green building management to engineering production and construction are analyzed to reduce the impact of high energy consumption and greenhouse gases on the environment. Through the analysis of (Building Information Modeling) BIM calculation and intelligent management, the development trend of future project management is summarized. Finally, taking Hangzhou e-Sports Center as an example, it verifies the necessity of designing according to green building design standards in the design stage, and expands internal management and dynamic monitoring of the whole process of project implementation to ensure management efficiency. The research results can provide new ideas and possibilities for the innovation of construction project management, and promote and disseminate these new technologies to promote the healthy development of the construction industry in the future.